Assessment of the Satellite Rainfall Data at Nam Theun 2 Catchment Area, Nakai District, Khammouane Province. - PHONGSA, Daovy (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
Nam Theun 2 Reservoir, located in National Conserve Park Nakai, covers a watershed of 4013 km2 and comprises 12 hydrological stations to support the rainfall data for reservoir management during tropical storms and flood states. It always faces problems during the rainy season with data transmission or lack of data for many days from the local rainfall station to the central server, and it is at high risk of lacking data during tropical storms. The purpose of this study is to verify the accuracy of using satellite rainfall data in the Nam Theun 2 reservoir area as a substitute for missing rainfall station data. This is aimed at providing information for water management in the reservoir to reduce associated risks. The method of this study used Google Earth Engine (GEE) and Climate Engine, which are geospatial processing services. The Earth Engine has been a public extensive data catalog for more than 40 years and has been active since 1970. The data was collected by using NSE (Nash-Sutcliffe Efficiency), indicating a perfect fit. PBIAS (Percent Bias). R2 (Coefficient of Determination) RSR (Root Mean Square Error) is a statistical measure quantifying the difference between predicted and actual values. The result of this comparison between satellite data and ground data for monthly rainfall CFSR is the best value NSE=0.91, PBIAS = -8.38, R2= 0.91and RSR= 0.15. for daily rainfall for CHIRPS is the best value NSE=0.52, PBIAS = 11.86 , R2= 0.60 and RSR= 0.68. the temperature is hifh accuracy the value of NSE = 0.99 , PBIAS = 6.00, RSR = 0.08, R2 = 0.99. In this study, it is observed that the use of satellite rainfall data is accurately satisfactory to good performance for assessing rainfall amounts at stations with missing data or in areas without rain gauge stations, to aid in water management in reservoirs.